A Frequency Analysis of Selected Modal Expressions in German and English Legal Texts - Nielsen, Jane Norre; Wichmann, Anne (HERMES - Journal of Language and Communication in Business, 2017)
This paper concerns the specialised use of written English and German in texts relating to contract law. It is based on corpora of original texts and examines specifically the way in which obligation is expressed in the two languages. The text types on which the present analysis is based are contracts and judgements.